2015
DOI: 10.1002/mds.26284
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of resting state networks in spinocerebellar ataxia type 2

Abstract: The SCA2 patients show significant alterations of the resting state networks, only partly explained by the atrophy. The default mode network is the only resting state network that shows also supratentorial changes, which appear unrelated to the cortical gray matter volume. Further studies are needed to assess the clinical significance of these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Cerebellar clusters of significantly reduced functional connectivity have been recently reported by Cocozza et al (2015) only in the default mode network, executive control network and right fronto-parietal network in patients with SCA2. However, this study used a different resting-state approach (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cerebellar clusters of significantly reduced functional connectivity have been recently reported by Cocozza et al (2015) only in the default mode network, executive control network and right fronto-parietal network in patients with SCA2. However, this study used a different resting-state approach (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…However, this study used a different resting-state approach (i.e. ICA) limited to investigate connectivity within specific functional networks (Cocozza et al, 2015). In the present study, by using a whole-brain approach, we provide additional evidence that extensive and segregated functional brain changes may occur as the result of the SCA2 degenerative process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, microstructural abnormalities measured by diffusion weighted imaging have been detected in the cerebellum and the pons28 as well as cortical alterations in SCA2 patients 10, 11, 29. Functional MRI in resting‐state modus further shows changes of cerebellar but also fronto‐ and parietal connectivity networks related to cognitive and motor performance 30, 31. No multimodal MRI data other than macroanatomical measurements exist for the preclinical stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Proton magnetic resonance spectrometry showed a decreased of NAA in the pons and cerebellar hemispheres 50, 51. Finally, a resting state functional magnetic resonance imaging study, corrected for atrophy, showed, besides disruption of the cerebellar component of the major resting state networks, supratentorial involvement for the default‐mode network 52. Dopaminergic transmission studied by beta‐CIT, a presynaptic dopamine reuptake site ligand, and iodobenzamide (IBZM), a postsynaptic dopamine D2 receptor ligand, was found to be abnormal even in patients without parkinsonian features 53, 54.…”
Section: Imagingmentioning
confidence: 93%